An Evaluation of Research on Integrated Product Development - Gerwin, Donald; Barrowman, Nicholas J. (Management Science, 2002)
Integrated Product Development (IPD) creates overlap and interaction between activities in the new product development process and, because this increases the need to coordinate, compensates through other aspects of the new product development process (e.g., integrated tools), product definitions (e.g., incremental development), organizational context (e.g., reduced task specialization), and teaming (e.g., cross-functional teams). Since IPD has become an important new standard for managing new product development, this paper's general aim is to evaluate the research that has been conducted on it. Our three specific objectives include first critiquing the IPD literature by identifying problems with empirical research and recommending solutions. There are concerns about the overall approach, conceptualizing and operationalizing IPD characteristics, and selecting performance objectives. Second, we conduct a meta-analysis to evaluate relationships between specific IPD characteristics and project performance. We indicate where relationships do or do not exist and identify variables that may moderate these relationships. Third, we offer suggestions for extending IPD research into studies of (a) the hierarchy of teams working on a project, (b) one company managing a portfolio of projects over time, and (c) two or more firms collaborating in a strategic alliance.